HARGA HEDONIK DAN PREFERENSI LEKSIKOGRAFIK PADA KONSUMSI SUSU SAPI CAIR DI YOGYAKARTA - Akoso, Galuh H.E.; Darwanto, Dwidjono Hadi; Waluyati, Lestari Rahayu (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2015)
The research on hedonic price and lexicographic preference in liquid milk consumption in Yogyakarta aims to identify: 1) the influencing factors of hedonic price, 2) the influencing factors of consumer's lexicographic preferences and 3) the influencing factors of liquid milk consumption with the insertion of lexicographic preference and hedonic price factors. Thirty household respondents were retrieved through judgement sampling in three locations namely Sidoarum, Kricak, and Tamantirto. Multiple regression results show that the following variables were significant to hedonic price: package design expectations and actual package design of the product, brand, and taste showed significant influences to Hedonic Price. Ordinal logit analysis on the influencing factors of consumer's lexicographic preference show that motivation and purchasing power were the significant variables affecting their lexicographic preferences. Analysis on the influencing factors affecting liquid milk consumption show that Hedonic Price, price perception, purchasing power, number of family members, frequency of milk consumption, Dummy of mother's occupation were the influential variables on liquid milk consumption.